Cultural Interference on the Use of English Second-Person Pronoun by Javanese Students - Retno Setya Budiasningrum (Universitas Pendidikan Mandalika, 2020)
Learning a language is not only about grammar and vocabulary but also about culture. Understanding culture allows language learners to give the right meaning to each word learned. English has a different culture from Indonesian. This study described the students' problems in using the second - person pronoun